Annual Plan Assam 1995-96 Vol. VII - Planning Commission (Planning Commission, 1995)
Physical Target and Achievement During The Annual Plan 1994-95 and Proposal for the Annual Plan 1995-96 Proposed for Spill over and ONGO Programme/Project Summary Statement Proposals for Programmes/Projects Draft Annual Plan 1995-96-Agriculture Annual Plan 1995-96 Projects Outlay Expenditure Soil Conservation Department, Drafts additive Plan 1995-1996 Hill Assam.
Vol. VII
Planning Commission